Peran Mediasi Motivasi Pada Pengaruh Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Pegawai Di Kantor Sekretariat DPRK Kota Subulussalam - Asmiadi Asmiadi; Syaiful Bahri; Sjahril Effendy Pasaribu (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The purpose of this study was to examine and analyze the influence of leadership and work environment on employee performance mediated by work motivation at the DPRK Secretariat office in Subulussalam City directly or indirectly. The approach used in this study is a causal approach. The population in this study were all employees of the DPRK Secretariat office in Subulussalam City. The sample in this study used a saturated sample of 32 employees of the DPRK Secretariat office in Subulussalam City. Data collection techniques in this study used documentation, observation, and questionnaire techniques. The data analysis technique in this study used a quantitative approach using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study using the PLS (Partial Least Square) software program. The results of this study indicate that leadership has a significant effect on employee performance, work environment has a significant effect on employee performance, work motivation has a significant effect on employee performance, leadership has a significant effect on work motivation, work has a significant effect on work motivation. And indirectly work motivation is able to mediate the influence of leadership on employee performance, work motivation is able to mediate the influence of the work environment on performance through employee satisfaction at the DPRK Secretariat office in Subulussalam City.